Neck circumference: An upcoming tool of adiposity indices - Adamu, Lawan; Asuku, Abdullahi; Taura, Magaji; Tela, Idris; Datti, Sa’adu; Imam, Aminu (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Obesity is one of the most significant contributors to ill health competing with under-nutrition and infectious diseases.Aims: The aims of the study were to determine the presence and level of sexual dimorphism in adiposity indices, correlation of neck circumference (NC) and body mass index (BMI) with other adiposity indices such as waist circumference (WC), waist-hip ratio (WHR) and waist-height ratio (WHtR) and also to encourage the uses of neck circumferences as valuable tool in assessing upper body central adiposity index.Settings and Design: The study population included 71 undergraduate participants (41 Males and 30 Females) with mean age of 22.68 4.23 years.Subjects and Methods: Anthropometric measurements of height, weight, NC, WC and HC were obtained following standard protocols.Statistical Analysis Used: Independentt-test and Pearson's correlation were employed to compare and find the relationship between the variables, using SPSS version 17. Significance level was considered atP≤ 0.05.Results: The result shows that there was statistically significant (P< 0.05) sexual dimorphism in mean WC, WHR and NC between the sexes. BMI showed strongest correlation with WHtR (r= 0.8,P< 0.001) followed by HC (r= 0.7,P< 0.001), WC (r= 0.7,P< 0.001). On the other hand the NC shows a significant correlation (P < 0.05) with all the variables.Conclusions: Despite the low level of correlation of NC with other adiposity indices compared to the BMI, the NC may serve as an important tool for the assessment of upper body adiposity.
Keywords: Adiposity indices; anthropometry; neck circumferences; Nigeria; obesity